Labor Supply in the Extended Household: Economies of Scale, Self-Selection and the Intrahousehold Distribution of Resources in South Africa - (:unkn) unknown (My University, 2024)
This article studies labor supply in the extended household (composed of two families living together). The extended household structure affects the incentives to work of household members for at least three reasons: economies of scale, cash transfers between the families living in the extended household, and easier childcare arrangements. We develop a structural model incorporating these components and taking into account the self-selection process into extended households. We then estimate this model with South African data and provide an explanation for the differences in participation rates between nuclear and extended households.
Keywords: African Research